Successful cerclage on cervix in the mid trimester: case report - Shaheed, Saika; Haque, Munima; Haider, Rebeka (International Journal of Research in Medical Sciences, 2019)
Cervical cerclage (CC) has been utilized for the cure of loss in second trimester pregnancy. The detection of cervical incompetency is problematic normally having repeated second trimester demise or early preterm delivery after cervical dilatation without pain having no bleeding, contractions, or other reasons for repeated loss in pregnancy. This study was performed at a tertiary care hospital in Dhaka, Bangladesh. These are 2 cases of patients undergoing emergency mid-trimester cerclage for advanced cervical dilatation with protruding membranes in 2016 and 2017. The 1st case patient was at 22 weeks of gestation and was admitted into hospital due to short history of lower abdominal pain and per vaginal bleeding. Vaginal inspection showed the cervix was dilated 1.5 cm. At 37 weeks of pregnancy she gave birth to a healthy female newborn by caesarean section and McDonald suture was removed. After delivery, mother and baby both were in good health. The 2nd case was of a patient of 26 years of age, second gravida, 24 weeks pregnant due to ovulation induction drug, who had a history of an abortion at 10 weeks. At her 24 weeks of pregnancy, she complained of profuse P/V whitish discharge and lower abdominal pain. It was found cervix was 2.5 cm dilated and bulging of membrane. Immediately McDonald suture was given. Patient was clinically improved, and USG showed OS is closed, length of the cervix is about 4.4 cm. At 32 weeks patient came with a complaint of rupture of membrane, then emergency caesarean section was done. A healthy premature female baby weighted 1.8 kg was delivered by vertex presentation. After operation, cerclage was removed. After delivery mother and baby both were in good health. Satisfactory neonatal result may be achieved in women having cervical deficiency in second-trimester pregnancy after emergency CC.